DOMINASI MOTIVASI KERJA, KOMPENSASI, DAN BUDAYA ORGANISASI TERHADAP LOYALITAS TENAGA KEPENDIDIKAN: STUDY KASUS - Bisma Arianto (HELPER, 2022)
The success of higher education is not only determined by capital, technology, or infrastructure, but is also determined by human resource factors. This study to determine the effect of work motivation, compensation, and organizational culture on the loyalty of education staff at Universitas PGRI Adi Buana Surabaya. The hypothesis in this study is that work motivation, compensation, and organizational culture have a simultaneous effect on the loyalty of education staff at Universitas PGRI Adi Buana Surabaya. 80 education staff at Universitas PGRI Adi Buana Surabaya were involved in this study through purposive sampling. Data was collected through a closed questionnaire distributed online. The questionnaire consists of 8 questions on work motivation, 10 questions on compensation, 8 questions on organizational culture, and 8 questions on job loyalty given to education staff. Data were analyzed through multiple linear regression using SPSS 20.0. The results of data analysis using SPSS obtained the value of Fcount = 26.979 > Ftable. This shows that simultaneously work motivation, compensation, and organizational culture affect the work motivation of education staff at Universitas PGRI Adi Buana Surabaya. For this reason, it is necessary to carry out further study by adding other variables as independent variables to see their effect on the loyalty of education personnel as the dependent variable. In addition, the research sample can use all education staff in the PGRI Adi Buana University Surabaya.